Islamic Education and Indoctrination: The Case in Indonesia - Tan, Charlene (Routledge Research in Education, 2011)
Islamic schools, especially madrasahs, have been viewed as sites of indoctrination for Muslim students and militants. Some educators and parents in the United States have also regarded introductory courses on Islam in some public schools as indoctrinatory. But what do we mean by "indoctrination"? And is Islamic education indoctrinatory? This book critically discusses the concept of indoctrination in the context of Islamic education. It explains that indoctrination occurs when a person holds to a type of beliefs known as control beliefs that result in ideological totalism. Using Indonesia as an illustrative case study, the book expounds on the conditions for an indoctrinatory tradition to exist and thrive. Examples include the Islamic school co-founded by Abu Bakar Ba'asyir and the militant organisation Jemaah Islamiyah. The book further proposes ways to counter and avoid indoctrination through formal, non-formal, and informal education. It argues for the creation and promotion of educative traditions that are underpinned by religious pluralism, strong rationality, and strong autonomy. Examples of such educative Muslim traditions in Indonesia will be highlighted. Combining philosophical inquiry with empirical research, this book is a timely contribution to the study of contemporary and often controversial issues in Islamic education.